A Multifunctional Reconfigurable Absorber Enabled by Graphene and Shape Memory Alloy. Issue 5 (20th December 2022) - Peng, Jinqiang; She, Ying; Su, He; Ji, Chen; Huang, Cheng; Luo, Xiangang
Abstract: Reconfigurable absorbers have attracted much interest owing to their dynamic reflection manipulation property. In this work, a novel multifunctional reconfigurable absorber, which can be flexibly switched among wideband absorption mode, frequency‐reconfigurable narrowband absorption mode, and amplitude‐controllable absorption mode, is proposed and demonstrated. This absorber employs the graphene layer for tuning its reflection magnitude, while the springs‐using shape memory alloy (SMA) is adopted to support the whole absorber for dynamically controlling absorption frequency through height regulation. The above functionality switching is realized by the bias voltage applied to the graphene layer and the loaded SMA springs. The reconfigurable absorption performance is experimentally verified, and the corresponding results show that such an absorber can generate wideband absorption in the range of 3.6–18 GHz. By tuning the height of the loaded SMA springs, it will be switched to the narrowband absorption state and its absorption peak frequency can be dynamically tuned from 8.7 to 13.5 GHz. When further changing the graphene resistance, the reflection amplitude can be also controlled in both wide‐ and narrow‐band absorption modes. In addition, the absorber also performs well under circumstances of different polarizations, which may have promising prospects in electromagnetic protection and camouflage fields. Abstract : In this work, a novel multifunctional reconfigurable absorber is proposed, which can be flexibly switched among wideband absorption mode, frequency‐reconfigurable narrowband absorption mode, and amplitude‐controllable absorption mode. This absorber employs graphene for tuning its reflection magnitude, while a springs‐using shape memory alloy (SMA) is adopted to support the whole absorber for dynamically controlling absorption frequency through height regulation.